2017
DOI: 10.1093/ofid/ofx162.123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Infectious Diseases Consultation on Mortality in Patients with Candidemia

Abstract: BackgroundAn infectious diseases (ID) consultation is often, but not always, obtained to help guide treatment of patients with candidemia. We examined if ID consultation affected patient outcome in patients with culture positive candidemia.MethodsWe assembled a retrospective cohort of 1,873 cases of candidemia in patients hospitalized in our academic tertiary care hospital from 2002 to 2015. We collected data on comorbidities, predisposing factors; antifungal therapy, survival and ID consult. Patients who died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
1
Order By: Relevance
“…Besides antifungal therapy, adequate source control is an important component of appropriate candidemia management. While previous research has reported that removal of CVC was more frequent in the IDC group than in the non-IDC group [1316, 26], our results showed no statistical difference in numbers of removal of CVC between both groups. In our study, we found that the IDC group had a statistically higher proportion of the removal of peripheral-line than the non-IDC group (OR = 2.91; 95% CI = 1.21–6.97; P = 0.013), which, to the best of our knowledge, has not been reported previously.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Besides antifungal therapy, adequate source control is an important component of appropriate candidemia management. While previous research has reported that removal of CVC was more frequent in the IDC group than in the non-IDC group [1316, 26], our results showed no statistical difference in numbers of removal of CVC between both groups. In our study, we found that the IDC group had a statistically higher proportion of the removal of peripheral-line than the non-IDC group (OR = 2.91; 95% CI = 1.21–6.97; P = 0.013), which, to the best of our knowledge, has not been reported previously.…”
Section: Discussioncontrasting
confidence: 95%
“…In fact, the proportion of PLAC was higher in the IDC group than the non-IDC group (OR = 2.34; 95% CI = 1.13–4.87; P = 0.020). Similar to a past study [26], our study revealed that consultation with an ophthalmologist was conducted more often in the IDC group then in the non-IDC group (OR = 6.68; 95% CI = 3.92–11.38; P < 0.001). For candidemia, the evaluation of endophthalmitis is thought to be a predictive factor for outcome improvement of candidemia, and contributes to an appropriate choice and duration of antifungal therapy [20, 27].…”
Section: Discussionsupporting
confidence: 87%